2010
DOI: 10.1111/j.1741-6787.2010.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nursing Best Practice Champions in Diffusing Practice Guidelines: A Mixed Methods Study

Abstract: Our research suggests that nursing best practice champions have a multidimensional role that is well suited to navigating the complexities of a dynamic health system to create positive change. Understanding of this role can help service organizations and the nursing profession more fully capitalize on the potential of champions to influence and implement evidence-based practices to advance positive patient, organizational, and system outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 38 publications
8
88
0
3
Order By: Relevance
“…One of the key facilitators of spread in this study, leading with passion and commitment, is consistent with other studies that have found leadership to be critically important for implementing and sustaining innovations [37-39,51]. This finding is consistent with studies inside and outside of health care settings that have shown that the commitment and attitude of leaders has a significant association with the acceptance and use of new innovations [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…One of the key facilitators of spread in this study, leading with passion and commitment, is consistent with other studies that have found leadership to be critically important for implementing and sustaining innovations [37-39,51]. This finding is consistent with studies inside and outside of health care settings that have shown that the commitment and attitude of leaders has a significant association with the acceptance and use of new innovations [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…Existing ‘nursing champions’ should also be empowered to help diffuse best practice within existing generalist nurses [22], [70].…”
Section: Discussionmentioning
confidence: 99%
“…Poudarjena pa je tudi potreba po zadostni premišljenosti pri načinu integracije kvantitativne in kvalitativne metodologije oziroma izbor ustreznega raziskovalnega načrta integracije metod glede na raziskovalni problem, upravičena uporaba kvalitativne raziskovalne faze ter zadostna upravičenost uporabe integracije metod glede na raziskovalni problem. 21 raziskav poudarja pomen nadaljnjega raziskovanja, in sicer v obliki priporočil za ponovitev raziskave na sorodnih ali kontrastnih populacijah (18), nadaljnje raziskovanje integracije metod v spletnem raziskovanju (36), uvedbo integracije metod v postopku evalvacije kakovosti novega merskega instrumenta (30), nadaljnja raziskovanja uporabe integracije metod pri sistematični evalvaciji promocijskih zdravstvenih programov (12,15,42,43) in razširitev možnosti uvedbe integracije metod v klinično prakso kot podpore pri razvoju na dokazih podprte prakse (44,38,34,41,39,37,48,45). Mortenson in Oliffe (31) izpostavljata potrebo po nadaljnjem raziskovanju integracije metod na področju delovne terapije, Andrew in Halcomb (10) na področju patronažnega zdravstvenega varstva in Bushy (13) na področju raziskovanja zdravja in zdravstvene nege na podeželju.…”
Section: Razpravljanjeunclassified